TRADISI BERFILSAFAT DALAM KARYA SASTRA PESANTRAN (Kajian Filologis Atas Naskah Dewi Maleka) - Said, Nur (ADDIN, 2012)
Pesantren (Islamic boarding school) with a strong tradition often get this claim as a conservative institution, traditional, and as far from the ratio so counter to the philosophy. This short paper will try to discuss a number of markers that boarding schools are also familiar with the problems of philosophical discourse as expressed in the ancient manuscript Dewi Maleka known as part of the Islamic literary of pesantern. This article discusses only two issues: (1) The description of Dewi Maleka manuscript in terms of its codicology?; (2) What kind of philisophical values in the content of of Dewi Maleka manuscript? The paper was analysed by philological approach through many steps: (a) Inventory of manuscripts for consideration in the determination of the manuscript, (b) Creating a text description in the frame of codicology, (c) study of the text that relefan to the current social context, will be a concern in the process. This paper concludes: (1) The Dewi Maleka manuscript is part of pesantren literature that containing moral teachings and wisdom of life in Islamic nuances. Therefore it can be used as an alternative to the basic framework of the development of Islamic philosophy; (2) The philosophical discourse often seems a bit complicated and heavy, but through the Dewi Maleka manuscript, life wisdom teachings delivered through dialogue, full of touching stories, entertaining and not patronizing, (3) The stories that illustrated in the Dewi Maleka manuscript also can be used as an alternative childrenâs moral education, so that the moral values of life can be internalized into oneâs personal with no coercion (doctrinal), but rather with awareness (conscientization) in the form of stories. Keywords: Dewi Maleka Manuscript, Pesantren literature, Pholosophicl Tradition